Bilateral agreement for the period 2007/2013 Socrates programme: higher education (Erasmus) between Università degli Studi Roma Tre and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Socrates programme; - Subject area: Political sciences; History.